Absence of recurrence in Fourier–Fourier transformed Vlasov–Poisson simulations. (23rd July 2018) - Klimas, Alexander J.; Viñas, Adolfo. F.
Abstract : It is known that the filtered, doubly Fourier transformed, Eulerian Vlasov–Poisson simulation method does not exhibit any effects of recurrence. It has not been understood why this is so. It is shown that there is only one boundary in this simulation method where user input is allowed and that the appearance or not of recurrence depends on the character of the boundary data that are imposed. Examples are given that show that the choice of boundary data that leads to recurrence-free simulations does not degrade the accuracy of Landau damping simulations.